PENGENALAN LITERASI KEUANGAN DIGITAL PADA PESANTREN DARUL ARAFAH RAYA - Nicky Hutapea; Nurganda Siregar; Nova Azahra; Mustika Dewi; Daniel Tampubolon (Pengabdian Deli Sumatera, 2023)
Abstract In the digital era, everyone is faced with financial literacy. Everyone's knowledge of financial literacy is different. The millennial generation is faced with the digital era which will become the successor to a nation that is literate about financial literacy and should be equipped with financial literacy knowledge so that they are able to compete and survive with today's advances. The millennial generation will later have personal responsibility for their finances. They will have responsibility for making important financial decisions in the future. This community outreach was conducted to provide information and understanding about financial literacy at the Darul Arafah Islamic Boarding School High School and increase awareness in planning and financial management. The method used is the question and answer method, lectures and discussions. Based on the results of the activity, there was a significant increase in financial literacy in Darul Arafah High School participants. This is evidenced from the results of questions and answers and discussions between speakers and participants. Keywords: Financial literacy, Financial education, Millennials, Financial behavior, Students